2016
DOI: 10.1002/ece3.1938
|View full text |Cite
|
Sign up to set email alerts
|

Dominant male song performance reflects current immune state in a cooperatively breeding songbird

Abstract: Conspicuous displays are thought to have evolved as signals of individual “quality”, though precisely what they encode remains a focus of debate. While high quality signals may be produced by high quality individuals due to “good genes” or favourable early‐life conditions, whether current immune state also impacts signalling performance remains poorly understood, particularly in social species. Here, we experimentally demonstrate that male song performance is impaired by immune system activation in the coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Females may select a male based on the information encoded in his songs, as different song traits may convey honest information about male characteristics or conditions (Nowicki, Peters & Podos, 1998; Gil & Gahr, 2002), such as their phenotypic (Richner, 2016) or genetic quality (Ferrer et al, 2015), and age (Espmark & Lampe, 1993; Kipper & Kiefer, 2010; but see Motes-Rodrigo, Labra & Lampe, 2017). In addition, song traits may reveal males’ physiological states (e.g., developmental stress (Nowicki et al, 2000; Spencer et al, 2005b), immune condition (York et al, 2016), body condition (Lampe & Espmark, 1994; Mountjoy & Lemon, 1996), or parasite levels (Spencer et al, 2005a)), as well as some of their behavioral characteristics (e.g., quality of the territories (Lampe & Espmark, 2003; Ritschard & Brumm, 2012), ability to provide paternal care (Buchanan & Catchpole, 2000; but see Rinden et al, 2000), or breeding experience (Lampe & Espmark, 1994; Motes-Rodrigo, Labra & Lampe, 2017)). Thus, it is not surprising that the fitness of males may be associated with song traits, such as song duration (Searcy et al, 2010), versatility (Järvi, 1983; Lampe & Espmark, 2003), or complexity (Soma & Garamszegi, 2011, but see Byers & Kroodsma, 2009; Potvin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Females may select a male based on the information encoded in his songs, as different song traits may convey honest information about male characteristics or conditions (Nowicki, Peters & Podos, 1998; Gil & Gahr, 2002), such as their phenotypic (Richner, 2016) or genetic quality (Ferrer et al, 2015), and age (Espmark & Lampe, 1993; Kipper & Kiefer, 2010; but see Motes-Rodrigo, Labra & Lampe, 2017). In addition, song traits may reveal males’ physiological states (e.g., developmental stress (Nowicki et al, 2000; Spencer et al, 2005b), immune condition (York et al, 2016), body condition (Lampe & Espmark, 1994; Mountjoy & Lemon, 1996), or parasite levels (Spencer et al, 2005a)), as well as some of their behavioral characteristics (e.g., quality of the territories (Lampe & Espmark, 2003; Ritschard & Brumm, 2012), ability to provide paternal care (Buchanan & Catchpole, 2000; but see Rinden et al, 2000), or breeding experience (Lampe & Espmark, 1994; Motes-Rodrigo, Labra & Lampe, 2017)). Thus, it is not surprising that the fitness of males may be associated with song traits, such as song duration (Searcy et al, 2010), versatility (Järvi, 1983; Lampe & Espmark, 2003), or complexity (Soma & Garamszegi, 2011, but see Byers & Kroodsma, 2009; Potvin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…) and in white‐browed sparrow weavers (York et al . ), or rattle duration in barn swallows Hirundo rustica (Dreiss et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…There are clearly constraints that limit song expression. For example, it has been shown that immunization can reduce song rate in collared flycatchers Ficedula albicollis ) and in white-browed sparrow weavers (York et al 2016), or rattle duration in barn swallows Hirundo rustica (Dreiss et al 2008). Recent studies in male European starlings found that inflammatory processes significantly decreased song rate and that the antibody production caused a moderate reduction of one particular mode of singing (undirected song rate, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…White-browed sparrow weaver males sing a distinct song type during the breeding season, known as the solo song (see Voigt et al 2006 for a spectogram of solo song). It is sung principally by dominant males, typically at dawn but also during the day, particularly during peak reproductive periods following high rainfall ( Wingfield and Lewis 1993 ; Voigt et al 2006 ; York 2012 ; York et al 2016 ). Extra-group males are known to intrude on occupied territories, where they have been observed producing solo song, eliciting vocal and physical responses (chases) from the resident dominant male.…”
Section: Introductionmentioning
confidence: 99%